A dataset for 15N natural abundance of soil ammonia volatilization - Lingyun Peng; Chaopu Ti; Bin Yin; Xiao Bai; Miao Li; Limin Tao; Xiaoyuan Yan (Scientific Data)
Abstract Investigating the sources of ammonia (NH3) in the atmosphere and the contribution of each source is essential for environmental pollution control. The presented dataset aims to provide 15N natural abundance (δ15N) data collected from different controlled treatments to fill the knowledge gap between insufficient data of soil δ15N-NH3 and accurately identifying atmospheric NH3 source apportionments. Our results showed that the overall δ15N-NH3 values emitted from soil ranged from −46.09 to 10.22‰, with an average of −26.81 ± 11.17‰. The mean δ15N-NH3 values under different nitrogen (N) application rates, N fertilizer types, air temperatures, soil moisture, soil pH, soil types, and land use types were −29.41 ± 10.91, −32.43 ± 6.86, −29.10 ± 10.04, −30.31 ± 6.18, −24.84 ± 13.76, −23.53 ± 7.66, and −14.57 ± 12.54‰, respectively. Significant correlations were observed between δ15N-NH3 values and soil pH, soil NO3 −-N concentration, and NH3 volatilization. This unique database provides basic data and evidence for the qualification of atmospheric NH3 source apportionments under different study area conditions.